Structural Stability of p(x)-Laplace Problems with Fourier Type Boundary Condition (Journal of Partial Differential Equations, 2019)
"We study the continuous dependence on coefficients of solutions of the nonlinear nonhomogeneous Fourier boundary value problems involving the p(x)-Laplace\r operator."
Keywords: Generalized Lebesgue and Sobolev spaces; Leray-Lions operator; weak solution; renormalized solution; Thermorheological fluids; continuous dependence; Fourier type boundary condition; Young measures.